Dancing for a Cause: Examining the Role of K-Pop in Mobilizing Youth for Charitable Giving during Ramadan - Agoes, Adrian; Khansa, Diva (Politeknik Pariwisata NHI Bandung, 2024)
This research investigates the success of the